A parceria de empresas educacionais de iniciativa privada com as redes municipais de educação do Sul de Minas Gerais - Cária, Neide Pena (2012)
The partnership between private companies and educational networks municipal education is a phenomenon that has been occurring in many municipalities in Brazil since the late 1990s. This thesis is dedicated to study this phenomenon in the municipalities that encompasses the South Regional Center of the State Department of Education of Minas Gerais, treated this research as South of Minas Gerais. We investigated what defines these partnerships. We take as an object the discourse analysis of companies identified as partners in the area surveyed. We use as device theoretical and methodological discourse analysis. Chosen as analytical corpus the discourse of the companies that circulates in the media / web, the home pages of educational enterprises. We made an analysis of data collected from in the empirical study and documentary research. The study showed that the phenomenon of partnership is a growing reality in Southern Minas. A discourse analysis of educational companies showed a speech advertising, marketing, which works to persuade through promise of education solutions and conducting a revolution public education, seducing municipal representatives at imaginary. The discursive mechanisms used indicate the use of marketing strategies and market interests as factors that define the phenomenon partnership by firms and by managers who welcome partnership, a supported uncritical view or interested in the imaginary and search results of evaluation to improve the position of their schools in ranking done nationally and internationally